(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The tendency of religious patterns in Indonesia is high egoism; it is considered that one’s religion is the most correct, while other religions do not contain truth or are heretical. Other religions must be defeated, and religion itself must be victorious. This pattern has influenced religious teaching and guidance both formally in the world of education and informally teaching religion in the family and society. This problem occurs not only among religious communities in Indonesia but also in the internal environment of religious communities. Not infrequently, there are unhealthy efforts to win one’s group and beat the others. Examining the Leadership Tasks of Religious Higher Education through a Learning Encounter in a Campaign of Religious Moderation was carried out effectively and well in building religious harmony. The Religious Moderation Campaign is conducted through encounter learning activities in tertiary institutions and seminars. Encounter Learning (encounter) is taught to Christian and non-Christian (Muslim and Buddhist) students. Speakers also brought in from sources whose religious Christianity and Islam. The campaign was carried out not only at state universities but also at Christian and Islamic universities. The method used is a qualitative analysis method. The results obtained by the Religious Moderation Campaign with learning encounters in which lectures, yells, and songs can foster religious harmony.